Розвиток економіко-інституційної бази вирішення конфліктів природокористування на прикладі лиману Куяльник - Рубель, О.Є. (Економічні інновації, 2013)
В роботі наведений аналіз сучасної методології стану та забезпечення розвитку економіко-інституційної бази вирішення конфліктів природокористування на прикладі лиману Куяльник. The paper describes the analysis of the current state of the methodology and the development of economic and institutional framework for environmental resolving conflicts example Estuary Kuyalnik.
The basis for managing the natural resource potential of the estuary into the formulation and implementation of River Basin Management Plan and the Great Basin Kuyalnik Kuyalnik estuary, which would facilitate the integrated management of natural resources Kuyalnik by all stakeholders.